Cerenkov Luminescence Imaging as a Modality to Evaluate Antibody-Based PET Radiotracers - D’Souza, Jimson W. (J Nucl Med, 2017)
Antibodies, and engineered antibody fragments, labeled with radioisotopes are being developed as radiotracers for the detection and phenotyping of diseases such as cancer. The development of antibody-based radiotracers requires extensive characterization of their in vitro and in vivo properties, including their ability to target tumors in an antigen-selective manner. In this study, we investigated the use of Cerenkov luminescence imaging (CLI) as compared with PET as a modality for evaluating the in vivo behavior of antibody-based radiotracers. Methods: The anti–prostate-specific membrane antigen (PSMA) huJ591 antibody (IgG; 150 kDa) and its minibody (Mb; 80 kDa) format were functionalized with the chelator 1,4,7-triazacyclononane-1-glutaric acid-4,7-diacetic acid (NODAGA) and radiolabeled with the positron-emitting radionuclide (64)Cu (half-life, 12.7 h). Immunoreactive preparations of the radiolabeled antibodies were injected into NCr nu/nu mice harboring PSMA-positive CWR22Rv1 and PSMA-negative PC-3 tumor xenografts. Tumor targeting was evaluated by both PET and CLI. Results: (64)Cu-NODAGA-PSMA-IgG and (64)Cu-NODAGA-PSMA-Mb retained the ability to bind cell surface PSMA, and both radiotracers exhibited selective uptake into PSMA-positive tumors. Under the experimental conditions used, PSMA-selective uptake of (64)Cu-NODAGA-PSMA-IgG and (64)Cu-NODAGA-PSMA-Mb was observed by CLI as early as 3 h after injection, with tumor-to-background ratios peaking at 24 (IgG) and 16 (Mb) h after injection. Targeting data generated by CLI correlated with that generated by PET and necropsy. Conclusion: CLI provided a rapid and simple assessment of the targeting specificity and pharmacokinetics of the antibody-based PET radiotracers that correlated well with the behavior observed by standard PET imaging. Moreover, CLI provided clear discrimination between uptake kinetics of an intact IgG and its small-molecular-weight derivative Mb. These data support the use of CLI for the evaluation of radiotracer performance.